Pengaruh Penggunaan Kulit Jeruk Nipis (Citrus Aurantifolia) Dengan Garam Sebagai Antiseptik Alami Dalam Menurunkan Jumlah Angka Kuman Pada Peralatan Makan - Inayah, Inayah; Hajar, Hasma (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Makassar, 2025)
Poor tableware hygiene can play an important role in the growth and spread of diseases and food poisoning. For this reason, the use of natural antiseptics made from lime peel (Citrus aurantifolia) with salt can be used to reduce the risk of contamination of pathogenic bacteria on tableware. This study aims to determine the effect of the use of lime peel antiseptic (Citrus aurantifolia) with salt in concentrations of 30%, 40%, and 50% on the reduction of the number of germs on spoons. This type of research uses a quasi-experimental method with a one group pre-post test design and is carried out in three replications. The total number of samples was 19 sample. The results of the study were analyzed using the paired samples test, the results were obtained with a concentration of 30%, a total decrease of 20 CFU/m2, and a sig value 0.057>0.05 means that there is no significant effect, for a concentration of 40% with a total decrease of 25 CFU/m2, and a sig value. 0.029<0.05 means that there is a significant influence, while the concentration is 50% with a total decrease of 29 CFU/m2 and a sig. 0.035<0.05 means that there is a significant influence on reducing the number of germs on the spoon. The use of natural antiseptics at concentrations of 30%, 40%, and 50% is not able to reduce the number of germs in tableware according to Indonesian Minister of Health Regulation No.1096/MENKES/PER/IV/2011 concerning Hygiene and Sanitation of Food Services, which is 0 (zero) CFU/m2. It is recommended for future researchers to focus not only on spoons, but also on various other types of cutlery such, as plates and glasses